Clinical comparison of percutaneous transforaminal endoscopic discectomy and unilateral biportal endoscopic discectomy for single-level lumbar disc herniation - Cheng, Xiaokang; Bao, Beixi; Wu, Yuxuan; Cheng, Yuanpei; Xu, Chunyang; Ye, Yang; Dou, Chentao; Chen, Bin; Yan, Hui; Tang, Jiaguang (Frontiers in Surgery, 2023)
Abstract Purpose: To compare the clinical outcomes of the percutaneous transforaminal endoscopic discectomy (PTED) and the unilateral biportal endoscopic discectomy (UBE) for the treatment of the single-level lumbar disc herniation(LDH). Materials and Methods From January 2020 to November 2021, 62 patients with single-level LDH were retrospectively reviewed. All the patients had spinal surgeries at the Affiliated Hospital of Chengde Medical University and Beijing Tongren Hospital, Capital Medical University. Among them, 30 patients were treated with UBE, and 32 were treated with PTED. The patients were followed up at least one year. Patient demographics and perioperative outcomes were reviewed before and after surgery. The Oswestry Disability Index (ODI), visual analog scale (VAS) for back pain and leg pain, and modified MacNab criteria were used to evaluate the clinical outcomes. X-ray examinations were performed one year after surgery to assess the stability of the lumbar. Results: The mean ages in the UBE and PTED groups were 46.7 years and 48.0 years, respectively. Compared to the UBE group, the PTED group had better VAS scores for back pain at 1 and 7 days a fter surgery (3.06±0.80 vs 4.03±0.81 P<0.05; 2.81±0.60 vs 3.70±0.79 P<0.05). The UBE and PTED groups demonstrated significant improvements in the VAS score for back and leg pain and ODI score, and no significant differences were found between the groups at any time after the first month(P>0.05). Although the good-to-excellent rate of the modified MacNab criteria in the UBE group was similar to that in the PTED group (86.7% vs 87.5%, P>0.05), PTED was advantageous in terms of the operative time, estimated blood loss, incision length, and length of postoperative hospital stay. Conclusions: Both UBE and PTED have favourable outcomes in patients with single-level LDH. However, PTED is superior to UBE in terms of short-term postoperative back pain relief and perioperative quality of life.